ENERGY ABSORPTION ANALYSIS OF FILAMENT-WOUND CFRP/AL HYBRID THIN-WALLED CIRCULAR TUBE UNDER AXIALLY CRUSHING - DONG BoYan; MA QiHua; YAO Yuan; HU PeiYuan; SUN ZeYu (Jixie qiangdu)
Combined simulation and test to investigate the collapse failure mode and energy absorption characteristics of wingding carbon fiber reinforced composite（CFRP[± 45°/90°]）/Al hybrid thin-walled circular tube under quasi-static axial compression load. Failure mode,Load-displacement curves and energy absorption characteristics were obtained under quasi-static axial crushing tests. A finite element model of hybrid tube was established according to samples. The simulation results with good agreement with the test were obtained by ABAQUS/Explicit,and the crushing failure behavior of the hybrid tube under quasistatic load was reproduced. Based on the simulation results,it was found that the initial crushing load,average crushing load,specific energy absorption and load efficiency of the mixing tube were increased by 97. 6%,93. 3%,57. 8% and 5. 9%,respectively. compared with the aluminum tube. The staged peaks and valleys of the crushing load were selected to analyze the shape of hybrid tube and the failure state of the fiber damage. The results show that when the hybrid tube is complete the fiber plays the main bearing role. In the crushing failure stage,the fiber damage failure mode changes with fiber winding angle,the crushing morphology of aluminum tube and the bonding interface state of CFRP/Al. Subsequently,the energy absorption characteristics of CFRP/Al hybrid circular tubes with three different structure forms were compared. It was found that hybrid circular tube with CFRP[90°/± 45°] wrapped the outside of the aluminum has the best energy absorption.